Skills Prediction for the South African Food and Beverages Manufacturing Sector - Megashnee Munsamy; Arnesh Telukdarie (GiLE Journal of Skills Development)
The high unemployment rate, especially among the youth in South Africa, necessitates addressing the skills requirements to meet the labour market demands. In South Africa, the Sector Education and Training Authorities are mandated to identify and provide the skills demanded. A quantitative approach of big data analytics is proposed for predicting the future skills of the South African food and beverages manufacturing sector. The source of big data is skills-related publications from the Elsevier Scopus database, for the period 1999 to 2020. Natural language processing, and word representation technique was applied to quantify and analyse year-on-year change of author and index keywords, subject areas and number of publications towards the determination of the future skills requirement. The analysis identified four vital skills: (1) entrepreneurship inclusive of digital skills; (2) data analytics inclusive of AI, simulation, and modelling; (3) digital tools and technologies implementation, and operation; and (4) sustainable operations skills of advanced process control, and energy, water, and resource optimisation. The identified skills were comparatively analysed with the World Economic Forum predictions for skills requirements for 2025, with the results aligning to the findings and validating the approach. The approach is applicable to any Sector Education Training Authority in South Africa. This enables enhanced skills planning to better prepare the South African workforce, especially youth, given the persistent challenges to completion of Grade 12 leading to access to higher education. It is acknowledged that youth with tertiary qualifications have a better chance of employment than those without, thus skills planning initiatives is essential. The skills gap cannot be instantaneously addressed but requires a long-term strategic effort from all stakeholders in the skills ecosystem. As a starting point in youth skills development, short courses to workshops to workplace training is a feasible option.